2022
DOI: 10.1038/s41598-022-16650-0
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the influence of gravity and the mechanical properties of elastin and collagen fibers on alveolar and lung pressure–volume curves

Abstract: The relationship between pressure (P) and volume (V) in the human lung has been extensively studied. However, the combined effects of gravity and the mechanical properties of elastin and collagen on alveolar and lung P–V curves during breathing are not well understood. Here, we extended a previously established thick-walled spherical model of a single alveolus with wavy collagen fibers during positive pressure inflation. First, we updated the model for negative pressure-driven inflation that allowed incorporat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…The shell is initially stress-free, and it is subject to the internal pressure . As shown in previous studies [19][20][21][22][23][24][25][26][27][28]29 elastin and collagen dominate the elastic behavior of the alveolar tissue, the contribution of interstitial cells being negligible 30,31 . It is well known that collagen and elastin bers form an interlinked random mesh in lung parenchyma.…”
Section: Mechanical Model Developmentmentioning
confidence: 69%
See 1 more Smart Citation
“…The shell is initially stress-free, and it is subject to the internal pressure . As shown in previous studies [19][20][21][22][23][24][25][26][27][28]29 elastin and collagen dominate the elastic behavior of the alveolar tissue, the contribution of interstitial cells being negligible 30,31 . It is well known that collagen and elastin bers form an interlinked random mesh in lung parenchyma.…”
Section: Mechanical Model Developmentmentioning
confidence: 69%
“…We propose a computational model for the lung based on the mechanical behavior of a single alveolus. Alveolar models and their generalizations have been successfully proposed to explain the pressurevolume response of the normal lung [21,28,29]. In particular, they allow to relate the macroscopic response of the lung (the pressure-volume curve) and the mechanical behavior of the alveolus.…”
Section: Mechanical Model Developmentmentioning
confidence: 99%
“…However, the strain plot indicated that the bottom of the lung experienced more strain than the rest of the structure. This discrepancy suggested that while the sides may have shifted more, the overall displacement of the bottom was constrained, possibly due to rigid body motion or structural stability mechanisms ( 46 , 47 ). As a result of these simulation findings, a practical adjustment was made in the experimental setup.…”
Section: Resultsmentioning
confidence: 99%
“…However, this hypothesis is questioned in some important ventilatory conditions in healthy subjects and particularly in patients. [48][49][50][51][52][53][54][55][56][57][58][59][60] A clear example in healthy subjects is exercise given the considerable flow values associated with high-amplitude and high-rate breathing.…”
Section: Nonlinearitiesmentioning
confidence: 99%
“…13 shows that in the normal standing position, and simply caused by the lung weight, there is a vertical distribution of pleural pressure. [52][53][54] The lower parts of the lungs are supporting the weight of their upper parts. As illustrated by ►Fig.…”
Section: Inhomogeneous Ventilation and Tissue Viscoelasticitymentioning
confidence: 99%